HTR+: a novel algorithm for identifying type and polycrystal of gas hydrates - Shi, Qiao; Lin, Ziyan; Qu, Yongxiao; Wu, Jianyang; Zhang, Zhisen (Journal of physics. Condensed matter, 2024)
In this work, the hierarchical topology ring (HTR+) algorithm, an extension of the HTR algorithm, was developed for identifying gas hydrate types, cage structures, and grain boundaries (GBs) within polycrystalline structures. Utilizing molecular dynamics trajectories of polycrystalline hydrates, the accuracy of the HTR+ algorithm is validated in identifying sI, sII and sH hydrate types, hydrate grains, and GBs in multi-hydrate polycrystals, as well as clathrate cages at GBs. Additionally, during the hydrate nucleation and growth processes, clathrate cages, hydrate type, hydrate grains and ice structures are accurately recognized. Significantly, this algorithm demonstrates high efficiency, particularly for large hydrate systems. HTR+ algorithm emerges a powerful tool for identifying micro/mesoscopic structures of gas hydrates, enabling an in-depth understanding of the formation mechanisms and properties of gas hydrates.